2011
DOI: 10.1177/1479164111416679
|View full text |Cite
|
Sign up to set email alerts
|

Effects of human endothelial gene polymorphisms on cellular responses to hyperglycaemia: Role of NOS3 (Glu298Asp) and ACE (I/D) polymorphisms

Abstract: The functional relevance of NOS3 and ACE genetic variations to endothelial cell function is largely unstudied. Here we tested the functional relevance of the NOS3 (Glu298Asp) polymorphism and ACE (I/D) polymorphism in endothelial cells in vitro. Our hypothesis was that these genetic polymorphisms alter endothelial cell sensitivity to glucose and 3-nitrotyrosine (3NT). Genotyped HUVECs were incubated with glucose, free 3NT or a combination of these two toxicants. Significant differences in glucose-induced cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 38 publications
0
7
0
1
Order By: Relevance
“…[25] The variant Asp allele for Glu298Asp polymorphism reduces NOS3 transcriptional activity and NO production in the endothelial cells. [26] …”
Section: Discussionmentioning
confidence: 99%
“…[25] The variant Asp allele for Glu298Asp polymorphism reduces NOS3 transcriptional activity and NO production in the endothelial cells. [26] …”
Section: Discussionmentioning
confidence: 99%
“…The role of gene polymorphism, in particular NOS3 (Glu298Asp), and end-product of glycosylation in the differential response of cells to hyperglycemia has been studied. It is shown that the presence of this genotype contributes to the development of endothelial-dependent vascular complications [42]. Several authors found that the G894T polymorphism of the NOS3 gene is a risk factor for coronary atherosclerosis and HD.…”
Section: Characteristics Of Endothelial Nitric Oxide Synthase Gene Pomentioning
confidence: 99%
“…Each of these proteins is intimately related to normal physiological and biochemical function of EC in vivo . Genetic variations in these proteins affect their functional responses and may increase the susceptibility of individuals with these polymorphisms to develop microvascular complications …”
Section: Genetic Risk Factors For Diabetic Vascular Complicationsmentioning
confidence: 99%
“…Although several genetic variations have been linked to cardiovascular disease, in many cases the mechanisms of each gene variation in disease progression have not been resolved. We have demonstrated that genetic polymorphisms at the level of NOS3 appear to significantly affect EC survival and responses to stress, suggesting that more detailed study of these and other relevant genes and focused mechanistic investigations are warranted to improve our understanding of the prevalence and progression of microvascular complications in diabetic heart disease. Furthermore, understanding the role of specific genetic polymorphisms in disease progression will enable us to develop tailored strategies for individualized treatment in the future.…”
Section: Functional Relevance Of Genetic Polymorphisms Of Nos3 and Vementioning
confidence: 99%
See 1 more Smart Citation